Reforming capitalist democracies: Which way? - Amit Bhaduri (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2020)
The debate about how to reconcile political with economic democracy is translated in the framework of wage- and profit-led growth in this paper. The inherent tension between providing sufficient profit incentive to motivate investment by the capitalist class and maintaining electoral accountability to the economically less privileged majority is examined through an analysis of policies towards raising the social wage. The paper shows how wider circumstances characterising a regime as wage- or profit-led is of consequence for determining the possibility of combining a higher profit share with a higher social wage through the effectiveness of such policies.
Keywords: E11; E12; H30; P16; H40; 330; Profit and wage led; social wage; investment; disinvestment; ideology